Tinjauan Literatur Sistematis Pengaruh Skin Factor terhadap Kurva Inflow Performance Relationship (IPR) dan Produktivitas Sumur Minyak - Asyer Yostian Sambara (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Well productivity decline due to formation damage in the near‑wellbore zone is reflected by increased positive skin factor, which shifts the inflow performance relationship (IPR) curve toward lower flow rates and reduces the productivity index (PI). This study applies a systematic literature review (SLR) to five selected articles published between 2023 and 2026 to examine the influence of skin factor on IPR curves and oil well productivity. Data sources include Google Scholar, Wiley Online Library, ScienceDirect, and MDPI. Findings indicate that skin factor affects transient flow rates, IPR curve displacement, and the economic feasibility of well stimulation. In low‑capacity reservoirs (k·h < 10,000 mD·m), stimulation reducing skin to negative values increases cumulative recovery by up to 35% and net present value (NPV) by more than 100%. In high‑capacity reservoirs (k·h > 60,000 mD·m), skin variation does not alter NPV. Mitigation strategies include acidizing, injection rate optimization, horizontal well configuration, and artificial lift based on nodal analysis.